2021
DOI: 10.3390/en14154428
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Simulation on Cooling Effect of Working Face under Radiation Cooling Mode in Deep Well

Abstract: Deep mining results in an increasingly serious hazard. Based on the principle of heat transfer and radiant cooling, a three-dimensional heat transfer model of the working face was established. The influence of the inlet airflow parameter, the surrounding wall temperature and other parameters on the temperature distribution of airflow along the working face were analyzed under the radiation cooling mode. The results show that the increment of airflow temperature in several sections along the working face decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
0
0
Order By: Relevance
“…Yi et al [ 11 ] analyzed the dynamic mechanism of tunnel AFT with the seasonal variation by the measured temperature distribution. Zhang et al [ 12 ] proposed a simulated model of the heat transfer at three-dimensional scale based on the radiation cooling mechanism, and analyzed the influence of the inflow parameters on AFT. Moreover, it was found that the stratified rock can lead to the significant difference in the temperature field, compared with the homogeneous assumption [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yi et al [ 11 ] analyzed the dynamic mechanism of tunnel AFT with the seasonal variation by the measured temperature distribution. Zhang et al [ 12 ] proposed a simulated model of the heat transfer at three-dimensional scale based on the radiation cooling mechanism, and analyzed the influence of the inflow parameters on AFT. Moreover, it was found that the stratified rock can lead to the significant difference in the temperature field, compared with the homogeneous assumption [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…He et al [9], based on the specific engineering background of Jiahe Coal Mine, proposed for the first time the establishment of a new cooling system with underground water inflow as the cold source, and innovatively proposed the high-temperature exchange machinery system (HEMS) and equipment. Zhang et al [10] established a three-dimensional heat transfer model of the working face, and they found that the greater the distance from the air flow inlet, the more obvious the cooling effect. Pokhrel et al [11] proposed that solar energy be used to deploy ice storage systems, and the ice generated can be used for cooling in deep mines through different heat exchangers.…”
Section: Introductionmentioning
confidence: 99%